Response to Letter to the Editor: “Recurrence and mortality after Pseudomonas aeruginosa bloodstream infection” - Felicity Edwards; Kevin B. Laupland (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

The Queensland Bloodstream Infections (QBSI) study: rationale, protocol development and future directions - Kevin B. Laupland; Felicity Edwards; Patrick N. A. Harris; Adam Irwin; Burcu Isler; Holly Hamilton; Sonali Coulter; Adam G. Stewart (Infectious Diseases, 2026)

Recurrence and mortality after Pseudomonas aeruginosa bloodstream infection: a population-based cohort study - Felicity Edwards; Michael Waller; Kevin B. Laupland (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Acoustic Indices Reveal Fundamental Differences in Daily Phenology of Tropical and Temperate Forest Soundscapes - Laura M. Berman; Santiago Perea; H. S. Sathya Chandra Sagar; Maia Persche; Grace Ingram; Tatiana Maeda; Natalie Yoh; Jorg Müller; Jens Schlüter; Nicolas Zapata; Ciara Wirth; Gonzalo Rivas‐Torres; et al. (Global Ecology and Biogeography, 2026)
Aim Forests support the majority of the planet's terrestrial biodiversity, and in recent years the characterisation of soundscapes has emerged as a powerful tool for understanding forest ecosystems, both in terms of ecology and for the purpose of conservation. But it is still poorly understood to what extent generalisations can be made about soundscapes in different parts of the world, and to what extent we should expect soundscapes to differ regionally. Here, we characterise the dominant acoustic features of forest soundscapes on a global scale and establish baseline expectations for how acoustic indices vary among biogeographic realms and biomes. Location Forests in Brunei, Ecuador, Gabon, Germany, Peru, Singapore, Sierra Leone and the USA, a dataset spanning two biomes and five out of six global biogeographic realms where forests occur. Time Period Two to five weeks of continuous audio data from each site collected between 2020 and 2024. Major Taxa Birds, amphibians, insects and mammals. Methods Stratifying data by time and frequency, we calculated four acoustic indices. Principal components analysis was used to compare the similarity of soundscapes across sites. Results Temperate and tropical forest soundscapes clustered separately in principal component analysis. Temperate forests had soundscapes which were uniformly loud during the day across all frequencies and were generally quiet at night. In contrast, all tropical locations had complex soundscapes during both day and night and had banding patterns suggestive of a high diversity of soniferous insects. These banding patterns were created by the unique soniferous community at each site, causing the ‘acoustic fingerprint’ of each site to be most similar to other sites in the same ecoregion and in the same biogeographic realm. The ‘acoustic fingerprints’ of temperate forest differentiated between ecoregions only when dawn was considered separately. Main Conclusions Our results stress the importance of using regional specific baseline data, as soundscapes are not necessarily comparable. Ecoacoustics is growing in popularity as an ecosystem monitoring tool, and understanding how forest soundscapes vary naturally across the globe can provide much needed context for studies that seek to understand factors that may disrupt or alter those soundscapes.

Community-onset bloodstream infection among people with opioid use disorders: a twenty-year population-based cohort study in Queensland, Australia - Kevin B. Laupland; Adam G. Stewart; Felicity Edwards; Patrick N. A. Harris; Sonali Coulter (Infectious Diseases, 2025)

Putting numbers to a metaphor: A Bayesian Belief Network with which to infer Soil Quality and Health - Kirsty L. Hassall; Joanna Zawadzka; Alice E. Milne; Ronald Corstanje; James A. Harris; A. Gordon Dailey; Aidan M. Keith; Margaret J. Glendining; S.P. McGrath; Lindsay C. Todman; Paul Alexander; Philippa Arnold; et al. (European Journal of Agronomy, 2025)

Determinants of time to positivity in bloodstream infections: an analysis of a population-based cohort in Queensland, Australia - Felicity Edwards; Michael Waller; Kevin B. Laupland (European Journal of Clinical Microbiology & Infectious Diseases, 2025)
Purpose Time to Positivity (TTP) measures the interval from incubation to bacterial growth detection in blood cultures. Although shorter TTP is associated with higher mortality, factors associated with TTP remain uncertain. Methods A retrospective cohort study was conducted among Queensland residents with positive blood cultures between 2000–2019. Incident bloodstream infections (BSIs) were identified using Pathology Queensland data, with demographic, clinical, and outcome data linked to state-wide databases. Results The study analysed 84,341 patients with monomicrobial BSI with a median patient age of 65.6 years (IQR 45.4–78.1), and most infections being community-associated (77.0%). Age showed a non-linear relationship with TTP, and male sex was linked with slightly higher TTP (Incidence Rate Ratio (IRR) 1.01; 95% Confidence Intervals (CI) 1.00–1.02; p = 0.011), reflecting a small but measurable association. Liver disease and malignancy were associated with lower TTP (IRR 0.93; 95% CI 0.91–0.95; p < 0.0001 and IRR 0.95; 95% CI 0.94–0.97; p < 0.0001 respectively), whilst diabetes showed no significant difference (IRR 1.01; 95% CI 1.00–1.02; p = 0.0840). Hospital onset infections exhibited longer TTPs (IRR 1.09; 95% CI 1.08–1.10; p < 0.0001). Conclusions There are several host characteristics associated with TTP that may in part explain the complex relationship between this variable and mortality. Beyond microbiological factors such as isolate type, TTP is also influenced by clinical variables including patient demographics and infection characteristics highlighting its potential as a prognostic marker. Further evaluation is needed to clarify its role in predicting patient outcomes and guiding tailored treatment strategies.

Tropical Land‐Use Change Disrupts Zeta‐Diversity Across Taxa - Edicson Parra‐Sanchez; Guillaume Latombe; Simon C. Mills; Jacob B. Socolar; Felicity A. Edwards; Diego Martinez‐Revelo; Oscar A. Perez‐Escobar; Robert W. Davies; Christopher G. Bousfield; Gianluca R. Cerullo; Jose Manuel Ochoa‐Quintero; Torbjørn Haugaasen; et al. (Global Change Biology, 2025)
Land‐use change causes community turnover via local extinction and colonisation of species, driving biotic homogenization or heterogenization at larger spatial scales. Quantification of these processes has focused on beta‐diversity metrics, which upweight rarity and overlook the role of widespread species. A key knowledge gap is understanding the impact of land‐use change on both rare and widespread species—zeta‐diversity—allowing the detection of statistical patterns and drivers based on community turnover across space. We sampled bird, dung beetle, and orchid communities in 341 plots across natural (Andean forests and paramo) and transformed habitats (pasturelands) spanning ~270 km north‐to‐south in the Colombian Andes. We detected major losses in species richness following land‐use conversion, which disrupts zeta‐diversity across elevation in two ways. First, biodiversity patterns are rewired such that bird and dung beetle communities become structured by dispersal ability, overriding the effects of natural biogeographical drivers (i.e., elevation) and landscape conditions (i.e., canopy cover). Second, land‐use change causes biotic homogenization across bird communities, with pasture retaining twice as many widespread species than natural habitats, and a four‐fold reduction in widespread dung beetle species pointing to subtractive heterogenization. Orchid communities show high community turnover in both natural and transformed habitat. Our results show that the effect of local deforestation has a doubly devastating impact simplifying communities and reducing widespread species. Transforming natural habitats into anthropogenic landscapes may substantially raise extinction risk for communities composed of both widespread and rare species, especially in orchids as the most sensitive taxon.

Risk of mortality in Fusobacterium species bloodstream infection from a large Australian cohort - Adam G. Stewart; Felicity Edwards; Patrick N. A. Harris; David L. Paterson; Kevin B. Laupland (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Epidemiology of biliary tract-associated bloodstream infections and adequacy of empiric therapy: an Australian population-based study - Ian Gassiep; Felicity Edwards; Kevin B. Laupland (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose Although the biliary tract is a common source of invasive infections, the epidemiology of cholangitis- and cholecystitis-associated bloodstream infection (BSI) is not well defined. The objective of this study was to determine the incidence, clinical determinants, microbiology of biliary tract-associated BSI, and predicted adequacy of common empiric therapy regimens. Methods All biliary tract-associated BSI in Queensland during 2000–2019 were identified using state-wide data sources. Predicted adequacy of empiric antimicrobial therapy was determined according to microbiological susceptibility data. Results There were 3,698 episodes of biliary tract-associated BSI occurred in 3,433 patients of which 2,147 (58.1%) episodes were due to cholangitis and 1,551 (41.9%) cholecystitis, for age- and sex-standardized incidence rates of 2.7, and 2.0 per 100,000 population, respectively. An increasing incidence of biliary tract-associated BSI was observed over the study that was attributable to an increase in cholangitis cases. There was a significant increased risk for biliary tract-associated BSI observed with advancing age and male sex. Patients with cholangitis were older, more likely to have healthcare associated infection, and have more comorbidities most notably liver disease and malignancies as compared to patients with cholecystitis. The distribution of infecting pathogens was significantly different with polymicrobial aetiologies more commonly observed with cholangitis (18.4% vs. 10.5%; p < 0.001). The combination of ampicillin/gentamicin/metronidazole was predicted to have the overall highest adequacy (96.1%), whereas amoxicillin/clavulanate had the lowest (77.0%). Amoxicillin/clavulanate (75.2% vs. 79.4%, p:0.03) and ceftriaxone/metronidazole (83.4% vs. 89.6%; p < 0.001) showed significantly inferior predicted adequacy for cholangitis as compared to cholecystitis. Conclusions Bloodstream infections related to cholecystitis and cholangitis exhibit different epidemiology, microbiology, and requirements for empiric therapy.

Pseudomonas stutzeri bloodstream infection is a prevailing community-onset disease with important mortality rates: results from a retrospective observational study in Australia - Juan P. Horcajada; Felicity Edwards; Silvia Fonio; Milagro Montero; Patrick Harris; David L. Paterson; Kevin B. Laupland (Infectious Diseases, 2024)

Evolving insights into the epidemiology of Moraxella species bloodstream infection from two decades of surveillance in Queensland, Australia - Jessica Schults; Felicity Edwards; Karina Charles; Adam D. Irwin; Claire M. Rickard; Patrick N. A. Harris; David L. Paterson; Kevin Laupland (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

High sensitivity of tropical forest birds to deforestation at lower altitudes - Simon C. Mills; Jacob B. Socolar; Felicity A. Edwards; Edicson Parra; Diego E. Martínez‐Revelo; Jose Manuel Ochoa Quintero; Torbjørn Haugaasen; Robert P. Freckleton; Jos Barlow; David P. Edwards (Ecology, 2023)
Habitat conversion is a major driver of tropical biodiversity loss, but its effects are poorly understood in montane environments. While community‐level responses to habitat loss display strong elevational dependencies, it is unclear whether these arise via elevational turnover in community composition and interspecific differences in sensitivity or elevational variation in environmental conditions and proximity to thermal thresholds. Here we assess the relative importance of inter‐ and intraspecific variation across the elevational gradient by quantifying how 243 forest‐dependent bird species vary in sensitivity to landscape‐scale forest loss across a 3000‐m elevational gradient in the Colombian Andes. We find that species that live at lower elevations are strongly affected by loss of forest in the nearby landscape, while those at higher elevations appear relatively unperturbed, an effect that is independent of phylogeny. Conversely, we find limited evidence of intraspecific elevational gradients in sensitivity, with populations displaying similar sensitivities to forest loss, regardless of where they exist in a species' elevational range. Gradients in biodiversity response to habitat loss thus appear to arise via interspecific gradients in sensitivity rather than proximity to climatically limiting conditions.

Determinants and outcomes of bloodstream infections related to obesity - Felicity Edwards; Kate Glen; Patrick N. A. Harris; David L. Paterson; Kevin B. Laupland (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Although obesity is a major healthcare problem that is increasing in many populations worldwide, there are limited studies that have examined its contribution to infectious diseases morbidity and mortality. The aim of this study was to examine the clinical determinants and outcomes of bloodstream infections among patients with obesity. All adults within the publicly funded healthcare system in Queensland, Australia, identified with a BSI during 2017–2019 were included and the presence of obesity was based on discharge International Classification of Diseases (ICD-10) codes. Clinical features, microbiology, and outcomes were compared among obese and non-obese subjects. A total of 24,602 incident BSI were identified among 21,613 Queensland residents; of which 4,579 (21.2%) and 17,034 (78.8%) were classified as obese or non-obese, respectively. Obese patients were less likely to have community associated infections and were more likely to be younger, female, have higher comorbidity scores, and have bone and joint or soft tissue infections as compared to non-obese subjects. Obese patients had a lower proportion of Escherichia coli BSI and higher proportions of b-haemolytic streptococci. Although obese patients had longer hospital admissions and more repeat incident BSI within 1 year, they had lower overall case fatality. In a logistic regression model, obesity was associated with a lower risk for 30-day case fatality (adjusted odds ratio 0.51, 95% confidence interval 0.45–0.58). Obesity is associated with significant differences in the determinants and outcome of BSI. Increasing rates of obesity is likely to influence the epidemiology of BSI in populations.

Pasteurella species bloodstream infections in Queensland, Australia, 2000–2019 - Kevin B. Laupland; Adam G. Stewart; Felicity Edwards; Patrick Harris; Claire Heney; Narelle George; Sonali Coulter; David L. Paterson (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Pasteurella species are infrequent but potentially severe causes of bloodstream infection (BSI). The objective of this study was to determine the incidence, risk factors, and outcomes of Pasteurella species BSI in a large Australian population. Retrospective, laboratory-based surveillance was conducted in Queensland, Australia (population ≈ 5 million) during 2000–2019, and clinical and outcome information was established by linkage to state hospital admissions and vital statistics databases. During more than 86 million person-years of surveillance, 272 incident Pasteurella species BSI occurred for an overall age- and sex-standardized annual incidence of 3.3 per million residents. The incidence of Pasteurella species BSI was highest in recent years and older individuals were at greatest risk. The median (interquartile range) Charlson Comorbidity Index was 2 (0–4) with scores of zero, 1, 2, and 3 + observed in 81 (30%), 37 (14%), 44 (16%), and 110 (40%) of cases. The 30-day all-cause case fatality was 9% (24/272) and patients who died had more comorbidities and were less likely to have community-associated disease. Although Pasteurella species are infrequent causes of BSI, older individuals and those with comorbidities are at highest risk. The burden of this disease may be expected to increase with an aging and more comorbid population.

Tropical land-use change alters trait-based community assembly rules for dung beetles and birds - Felicity A. Edwards; David P. Edwards; Keith C. Hamer; Tom M. Fayle (Oecologia, 2021)
Tropical rainforest disturbance and conversion are critical drivers of biodiversity loss. A key knowledge gap is understanding the impacts of habitat modification on mechanisms of community assembly, which are predicted to respond differently between taxa and across spatial scales. We use a null model approach to detect trait assembly of species at local- and landscape-scales, and then subdivide communities with different habitat associations and foraging guilds to investigate whether the detection of assembly mechanisms varies between groups. We focus on two indicator taxa, dung beetles and birds, across a disturbance gradient of primary rainforest, selectively logged rainforest, and oil palm plantations in Borneo, Southeast Asia. Random community assembly was predominant for dung beetles across habitats, whereas trait convergence, indicative of environmental filtering, occurred across the disturbance gradient for birds. Assembly patterns at the two spatial scales were similar. Subdividing for habitat association and foraging guild revealed patterns hidden when focusing on the overall community. Dung beetle forest specialists and habitat generalists showed opposing assembly mechanisms in primary forest, community assembly of habitat generalists for both taxa differed with disturbance intensity, and insectivorous birds strongly influenced overall community assembly relative to other guilds. Our study reveals the sensitivity of community assembly mechanisms to anthropogenic disturbance via a shift in the relative contribution of stochastic and deterministic processes. This highlights the need for greater understanding of how habitat modification alters species interactions and the importance of incorporating species’ traits within assessments.

Secondary forest fragments offer important carbon and biodiversity cobenefits - Fabio A. R. Matos; Luiz F. S. Magnago; Carlos Aquila Chan Miranda; Luis F. T. de Menezes; Markus Gastauer; Nathália V. H. Safar; Carlos E. G. R. Schaefer; Mônica P. da Silva; Marcelo Simonelli; Felicity A. Edwards; Sebastião V. Martins; João A. A. Meira‐Neto; et al. (Global Change Biology, 2020)
Tropical forests store large amounts of carbon and high biodiversity, but are being degraded at alarming rates. The emerging global Forest and Landscape Restoration (FLR) agenda seeks to limit global climate change by removing carbon dioxide from the atmosphere through the growth of trees. In doing so, it may also protect biodiversity as a free cobenefit, which is vital given the massive shortfall in funding for biodiversity conservation. We investigated whether natural forest regeneration on abandoned pastureland offers such cobenefits, focusing for the first time on the recovery of taxonomic diversity (TD), phylogenetic diversity (PD) and functional diversity (FD) of trees, including the recovery of threatened and endemic species richness, within isolated secondary forest (SF) fragments. We focused on the globally threatened Brazilian Atlantic Forest, where commitments have been made to restore 1 million hectares under FLR. Three decades after land abandonment, regenerating forests had recovered ~20% (72 Mg/ha) of the above‐ground carbon stocks of a primary forest (PF), with cattle pasture containing just 3% of stocks relative to PFs. Over this period, SF recovered ~76% of TD, 84% of PD and 96% of FD found within PFs. In addition, SFs had on average recovered 65% of threatened and ~30% of endemic species richness of primary Atlantic forest. Finally, we find positive relationships between carbon stock and tree diversity recovery. Our results emphasize that SF fragments offer cobenefits under FLR and other carbon‐based payments for ecosystem service schemes (e.g. carbon enhancements under REDD+). They also indicate that even isolated patches of SF could help to mitigate climate change and the biodiversity extinction crisis by recovering species of high conservation concern and improving landscape connectivity.

The impact of secondary forest regeneration on ground-dwelling ant communities in the Tropical Andes - Matthew G. Hethcoat; Bethany J. King; Fernando Fernandez Castiblanco; Claudia M. Ortiz-Sepúlveda; Fabian Camilo Prada Achiardi; Felicity A. Edwards; Claudia Medina; James J. Gilroy; Torbjørn Haugaasen; David P. Edwards (Oecologia, 2019)

Optimizing carbon storage and biodiversity protection in tropical agricultural landscapes - James J. Gilroy; Paul Woodcock; Felicity A. Edwards; Charlotte Wheeler; Claudia A. Medina Uribe; Torbjørn Haugaasen; David P. Edwards (Global Change Biology, 2014)
With the rapidly expanding ecological footprint of agriculture, the design of farmed landscapes will play an increasingly important role for both carbon storage and biodiversity protection. Carbon and biodiversity can be enhanced by integrating natural habitats into agricultural lands, but a key question is whether benefits are maximized by including many small features throughout the landscape (‘land‐sharing’ agriculture) or a few large contiguous blocks alongside intensive farmland (‘land‐sparing’ agriculture). In this study, we are the first to integrate carbon storage alongside multi‐taxa biodiversity assessments to compare land‐sparing and land‐sharing frameworks. We do so by sampling carbon stocks and biodiversity (birds and dung beetles) in landscapes containing agriculture and forest within the Colombian Chocó‐Andes, a zone of high global conservation priority. We show that woodland fragments embedded within a matrix of cattle pasture hold less carbon per unit area than contiguous primary or advanced secondary forests (>15 years). Farmland sites also support less diverse bird and dung beetle communities than contiguous forests, even when farmland retains high levels of woodland habitat cover. Landscape simulations based on these data suggest that land‐sparing strategies would be more beneficial for both carbon storage and biodiversity than land‐sharing strategies across a range of production levels. Biodiversity benefits of land‐sparing are predicted to be similar whether spared lands protect primary or advanced secondary forests, owing to the close similarity of bird and dung beetle communities between the two forest classes. Land‐sparing schemes that encourage the protection and regeneration of natural forest blocks thus provide a synergy between carbon and biodiversity conservation, and represent a promising strategy for reducing the negative impacts of agriculture on tropical ecosystems. However, further studies examining a wider range of ecosystem services will be necessary to fully understand the links between land‐allocation strategies and long‐term ecosystem service provision.

Land‐sharing versus land‐sparing logging: reconciling timber extraction with biodiversity conservation - David P. Edwards; James J. Gilroy; Paul Woodcock; Felicity A. Edwards; Trond H. Larsen; David J. R. Andrews; Mia A. Derhé; Teegan D. S. Docherty; Wayne W. Hsu; Simon L. Mitchell; Takahiro Ota; Leah J. Williams; et al. (Global Change Biology, 2014)
Selective logging is a major driver of rainforest degradation across the tropics. Two competing logging strategies are proposed to meet timber demands with the least impact on biodiversity: land sharing, which combines timber extraction with biodiversity protection across the concession; and land sparing, in which higher intensity logging is combined with the protection of intact primary forest reserves. We evaluate these strategies by comparing the abundances and species richness of birds, dung beetles and ants in Borneo, using a protocol that allows us to control for both timber yield and net profit across strategies. Within each taxonomic group, more species had higher abundances with land‐sparing than land‐sharing logging, and this translated into significantly higher species richness within land‐sparing concessions. Our results are similar when focusing only on species found in primary forest and restricted in range to Sundaland, and they are independent of the scale of sampling. For each taxonomic group, land‐sparing logging was the most promising strategy for maximizing the biological value of logging operations.

Reliable, verifiable and efficient monitoring of biodiversity via metabarcoding - Yinqiu Ji; Louise Ashton; Scott M. Pedley; David P. Edwards; Yong Tang; Akihiro Nakamura; Roger Kitching; Paul M. Dolman; Paul Woodcock; Felicity A. Edwards; Trond H. Larsen; Wayne W. Hsu; et al. (Ecology Letters, 2013)
To manage and conserve biodiversity, one must know what is being lost, where, and why, as well as which remedies are likely to be most effective. Metabarcoding technology can characterise the species compositions of mass samples of eukaryotes or of environmental DNA . Here, we validate metabarcoding by testing it against three high‐quality standard data sets that were collected in Malaysia (tropical), China (subtropical) and the United Kingdom (temperate) and that comprised 55,813 arthropod and bird specimens identified to species level with the expenditure of 2,505 person‐hours of taxonomic expertise. The metabarcode and standard data sets exhibit statistically correlated alpha‐ and beta‐diversities, and the two data sets produce similar policy conclusions for two conservation applications: restoration ecology and systematic conservation planning. Compared with standard biodiversity data sets, metabarcoded samples are taxonomically more comprehensive, many times quicker to produce, less reliant on taxonomic expertise and auditable by third parties, which is essential for dispute resolution.

Trophic Flexibility and the Persistence of Understory Birds in Intensively Logged Rainforest - DAVID P. EDWARDS; PAUL WOODCOCK; ROB J. NEWTON; FELICITY A. EDWARDS; DAVID J. R. ANDREWS; TEEGAN D. S. DOCHERTY; SIMON L. MITCHELL; TAKAHIRO OTA; SUZAN BENEDICK; SIMON H. BOTTRELL; KEITH C. HAMER (Conservation Biology, 2013)
Effects of logging on species composition in tropical rainforests are well known but may fail to reveal key changes in species interactions. We used nitrogen stable‐isotope analysis of 73 species of understory birds to quantify trophic responses to repeated intensive logging of rainforest in northern Borneo and to test 4 hypotheses: logging has significant effects on trophic positions and trophic‐niche widths of species, and the persistence of species in degraded forest is related to their trophic positions and trophic‐niche widths in primary forest. Species fed from higher up the food chain and had narrower trophic‐niche widths in degraded forest. Species with narrow trophic‐niche widths in primary forest were less likely to persist after logging, a result that indicates a higher vulnerability of dietary specialists to local extinction following habitat disturbance. Persistence of species in degraded forest was not related to a species’ trophic position. These results indicate changes in trophic organization that were not apparent from changes in species composition and highlight the importance of focusing on trophic flexibility over the prevailing emphasis on membership of static feeding guilds. Our results thus support the notion that alterations to trophic organization and interactions within tropical forests may be a pervasive and functionally important hidden effect of forest degradation. Flexibilidad Trófica y la Persistencia de Aves de Sotobosque en un Bosque Lluvioso Talado Intensivamente

Engaging People in Meaningful Problem Solving - Felicity N. Edwards; Michael L. Gibeau (Conservation Biology, 2013)

Assessing trophic position from nitrogen isotope ratios: effective calibration against spatially varying baselines - Paul Woodcock; David P. Edwards; Rob J. Newton; Felicity A. Edwards; Chey Vun Khen; Simon H. Bottrell; Keith C. Hamer (The Science of Nature, 2012)

The Value of Rehabilitating Logged Rainforest for Birds - DAVID P. EDWARDS; FELICITY A. ANSELL; ABDUL H. AHMAD; REUBEN NILUS; KEITH C. HAMER (Conservation Biology, 2009)
The recent advent of carbon crediting has led to a rapid rise in biosequestration projects that seek to remove carbon from the atmosphere through afforestation and forest rehabilitation. Such projects also present an important potential opportunity to reverse biodiversity losses resulting from deforestation and forest degradation, but the biodiversity benefits of different forms of biosequestration have not been considered adequately. We captured birds in mist nets to examine the effects of rehabilitation of logged forest on birds in Sabah, Borneo, and to test the hypothesis that rehabilitation restores avian assemblages within regenerating forest to a condition closer to that seen in unlogged forest. Species richness and diversity were similar in unlogged and rehabilitated forest, but significantly lower in naturally regenerating forest. Rehabilitation resulted in a relatively rapid recovery of populations of insectivores within logged forest, especially those species that forage by sallying, but had a marked adverse effect on frugivores and possibly reduced the overall abundance of birds within regenerating forest. In view of these results, we advocate increased management for heterogeneity within rehabilitated forests, but we strongly urge an increased role for forest rehabilitation in the design and implementation of a biodiversity‐friendly carbon‐offsetting market.